Real-world pharmacotherapy treatment patterns among patients diagnosed with postpartum depression in the United States - D. Claire Miller; Devika Chawla; Katherine Johansen Taber; Jennifer L. Payne; Andria L. Del Tredici (BMC Psychiatry)
Abstract Background Pharmacotherapy is one modality recommended to treat postpartum depression (PPD), but treatment patterns are not well characterized. In this study we characterized psychiatric medications used to treat PPD in real-world settings. Methods Two cohorts of patients diagnosed with PPD within 180 days of delivery between October 2015 and January 2022 were retrospectively studied using two U.S. claims databases (Symphony Health [SH], Myriad Genetics-Komodo Health [MGKH]). Prescription fills of select psychiatric medications in the 365 days after PPD diagnosis were assessed using pharmacy claims. Results The two cohorts (SH, MGKH) included 124,742 and 22,141 patients with PPD, respectively. Most patients with PPD (SH: 64.9%, MGKH: 76.4%) filled at least 1 prescription in the year following diagnosis; of those, 76.4% and 62.7%, respectively, discontinued treatment at least once. Medication changes were also common among treated patients, with 16.6% in SH and 18.3% in MGKH filling 3 or more unique psychiatric medications. In each cohort, selective serotonin reuptake inhibitors (SSRIs) comprised 72.2% of observed first-line treatments following PPD diagnosis, and sertraline was the most common first-line SSRI (39.4% and 41.4% of first-line treatments, respectively). Later-line therapies were not dominated by any single medication or medication class. Conclusions While the majority of patients with PPD were prescribed pharmacotherapy, treatment patterns were heterogeneous and characterized by frequent discontinuation and medication switching. These results suggest that first-line treatments may fail, and that some patients may need multiple medication trials to improve symptoms. Clinical trial number Not applicable.